Interpersonal Conflict as a Barrier to Job Performance among Librarians: The Mediating Role of Emotional Intelligence (Lead City International Journal of Library, Information & Communication Sciences, 2025)
This opinion based piece explores the critical role of emotional intelligence (EI) in managing conflict within library settings. Drawing a personal observations and theoretical insights, it argues that emotional intelligence is an indispensable tool for librarians to effectively handle interpersonal conflicts in libraries, enhance team works, and improve overall job performance. The discussion highlights common types of conflicts encountered in libraries, including those between staff and patrons, and how EI strategies such as empathy, active listening, and emotional regulation can address these challenges. By providing practical recommendations and illustrations of the benefits of EI through hypothetical scenarios, this article emphasizes the transformative potentials of emotional intelligence in resolving conflicts and fostering a positive library atmosphere for effective job performance among librarians. The piece recommends among others that EI training be integrated into professional development programmes of librarians, asserting that such initiatives can lead to more harmonious work environments, better job performance and better service delivery in libraries.